IgD attenuates the IgM-induced anergy response in transitional and mature B cells - Zahra Sabouri (Nature Portfolio, 2016)
Self-reactive B cells that are anergic express mainly IgD, yet the function of IgD is not clear. Here the authors analyse primary B cells from mice to show that IgD signalling attenuates self-antigen induced gene expression and promotes survival of anergic B cells that might go on to reactivate to foreign antigens and mutate away from self-reactivity.